FISH IN INDIGENOUS HEALING PRACTICES AMONG THE ILAJE OF COASTAL YORUBALAND OF NIGERIA: A HISTORICAL PERSPECTIVE - Ehinmore, O.M.; Ogunode, S.A. (European Scientific Journal, ESJ, 2013)
A recent historical survey of the Ilaje littoral communities located in the Western Niger Delta of Nigeria strongly indicated that, some indigenous healing devices with high level of potency had been evolved by the people over the years without being researched. The adoption of fishes in medical practices had resulted in potent socio–spiritual healing for ages. In spite of its enormous contributions to health care delivery, academics have not devoted much research focus on the area. As an antithesis to Western notion of no scientific ingenuity in pre – colonial African societies, the paper discusses the various medicinal devices, as well as the merits and problems of indigenous fish therapy among the Ilaje people in a typical African environment. It also suggests an inter–marriage of traditional with orthodox medical healing devices for a better health care delivery in the society.